2008
DOI: 10.1186/1472-6963-8-214
|View full text |Cite
|
Sign up to set email alerts
|

The emotional context of self-management in chronic illness: A qualitative study of the role of health professional support in the self-management of type 2 diabetes

Abstract: Background: Support for patient self-management is an accepted role for health professionals. Little evidence exists on the appropriate basis for the role of health professionals in achieving optimum self-management outcomes. This study explores the perceptions of people with type 2 diabetes about their self-management strategies and how relationships with health professionals may support this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 30 publications
6
81
0
1
Order By: Relevance
“…He/she needed to feel involved and receive support from the care provider during the course of the disease. The emotions associated with a chronic disease constituted a continuous process and the diabetic person needed the support of care staff during their emotional adaptation to the disease [22,23]. The image that the diabetic person had of the disease was influenced more by previous experiences than the information provided by the care staff [23].…”
Section: Care Encounters From the Individuals Perspectivementioning
confidence: 99%
“…He/she needed to feel involved and receive support from the care provider during the course of the disease. The emotions associated with a chronic disease constituted a continuous process and the diabetic person needed the support of care staff during their emotional adaptation to the disease [22,23]. The image that the diabetic person had of the disease was influenced more by previous experiences than the information provided by the care staff [23].…”
Section: Care Encounters From the Individuals Perspectivementioning
confidence: 99%
“…Patients with diabetes from an ethnic minority have added burdens in behaviour change, performing their daily activities of self-management within the context of social, family and cultural duties (Furler et al, 2008;Manderson & Kokanovic, 2009), language and cultural difficulties in communication with health care professionals (Jowsey, Gillespie, & Aspin, 2011) and racial discrimination (Komaric, Bedford, & van Driel, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…As it is a chronic disease, patients experience a strong shock when they receive the diagnosis, and become unsure about how to live with diabetes. As in the present study, the referred study also identified that the main changes that occurred because of the disease concerned eating and exercise habits, and that walking was the most common exercise modality adopted (17) .…”
Section: Discussionmentioning
confidence: 75%